2023
DOI: 10.1111/jir.13071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rope skipping exercise on physical, cardiovascular fitness and exercise tolerance in adolescent students with moderate intellectual disability

Abstract: BackgroundAdolescents with intellectual disabilities (ID) who live a sedentary lifestyle may lead to an increased risk of chronic cardiovascular disease in adulthood. The aim of this study is to investigate the effects of 8‐week progressive rope skipping training on physical, cardiovascular fitness and exercise tolerance of high school students with moderate ID.MethodsThirty‐four senior high school with ID (aged 15–18 years old) were randomised into experimental group received progressive skipping rope exercis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Additionally, RSE is not only cost-effective and enjoyable but also more suitable for widespread implementation in limited spaces compared to common activities like walking or running ( 28 ). Existing studies have demonstrated that an 8-week RSE can improve CRF among special needs children and increase autonomic activation in the prefrontal cortex associated with WM ( 29 , 30 ). Therefore, it is hypothesized that an 8-week RSE could positively impact both WM and CRF in children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, RSE is not only cost-effective and enjoyable but also more suitable for widespread implementation in limited spaces compared to common activities like walking or running ( 28 ). Existing studies have demonstrated that an 8-week RSE can improve CRF among special needs children and increase autonomic activation in the prefrontal cortex associated with WM ( 29 , 30 ). Therefore, it is hypothesized that an 8-week RSE could positively impact both WM and CRF in children with ADHD.…”
Section: Introductionmentioning
confidence: 99%
“…Jumping is an important skill for children because it offers anabolic stimulation to the musculoskeletal system (13). In addition, jump training has been linked to improved coordination and balance (14), and increased cardiorespiratory fitness (15). Unfortunately, because they are unable to jump or have limited jumping ability, most children with CP are unable to fully participate in activities that require jumping or reap the health advantages associated with jumping.…”
mentioning
confidence: 99%